Do people with intersecting identities report more high-risk alcohol use and lifetime substance use? - Demant, D.; Oviedo-Trespalacios, O.; Carroll, J.; Ferris, J.; Maier, L.; Barratt, Monica; Winstock, A. (Birkhaeuser Science, 2018)
© 2018 Swiss School of Public Health (SSPH+) Objectives: We examined protective and non-protective effects of disadvantaged social identities and their intersections on lifetime substance use and risky alcohol consumption. Methods: Data from 90,941 participants of the Global Drug Survey 2015 were analysed. Multivariable logistic regressions were used to calculate adjusted odds ratios for lifetime use of nine psychoactive substances, as well as high-risk/harmful alcohol use. Disadvantaged identities from three categories (ethnicity, sexual identity, gender), and interactions between these were compared. Results: Findings indicate that participants with disadvantaged ethnic and sexual minority identities are more likely to use psychoactive substances compared to their counterparts. The intersecting identity ‘disadvantaged ethnic identity and sexual minority’ appears to be protective compared to those with just one of these identities. While female gender appears to be highly protective in general, it is not protective among females with disadvantaged social identities. Conclusions: Stark disparities in substance use between different social identities and their intersections emphasise the importance of intersectionality theories in public health research intervention design. Future research on health equity, particularly substance use, should target individuals with intersecting identities.